Voice and swallowing alterations in neurological patients after brain aneurysm - Herreras Huamán, Vicente José; Yauyo López, Susan Leonor (Revista de Investigación en Logopedia, 2021)
The objective of the study was to determine the voice and swallowing disorders in patients with neurological deficiencies secondary to subarachnoid hemorrhage due to ruptured brain aneurysm. The study is descriptive in cross section; performed on 30 patients from the Guillermo Almenara Irigoyen National Hospital in Peru, who met the eligibility criteria. The quality of voice and swallowing was evaluated by means of the Clinical Evaluation of Voice and Swallowing in patients with Hemorrhagic Stroke using the sound level meter, laryngeal auscultation and pulse oximeter. The results obtained were, according to the quality of the voice: timbre 63.3% opaque, tone 86.7% low tone, intensity an intensity decreased by 90%; 86.7% duration is short. In the characteristics of the swallowing of the oral phase in food textures 83.3% deficient, number of chews 76.7% deficient, in time / duration of chewing 86.7% deficient and nutritional remains 90% present. Swallowing characteristics in the pharyngeal phase according to the number of swallows, 46.7% inadequate, according to cough and throat clearing, 36.7% present it and 73.3% presence of apnea. Degree of dysphonia 70% of Grade II. Dysphagia degree 60% have severe degree. Therefore, it is concluded that there are voice alterations with a predominance of opaque timbre, severe tone, decreased intensity and short duration, swallowing disorders in the oral phase and the presence of a high percentage of severe grade dysphagia and dysphonia of grade II.
Keywords: Aneurysm; Dysphagia; Dysphonia; Subarachnoid hemorrhage; Voice quality